On the crossing point between university and gender perspective: a provisory diagnosis in Bahía Blanca, Argentina (Praxis Educativa, 2018)
Universidad Nacional del Sur, founded in 1956 in the city of Bahía Blanca offers a broad educational options, structured in academic departments. Despite this, it does not have an institute or groups specialized in gender, or diversity perspective. The few actions related to these issues that occur, seem to do so outside, but not at the institutional level. According to two critical incidents, we will analyze how the power plots produced inside the university could make possible the research development, political actions and the presences of other gender subjectivities. The purpose is to address the tensions between inside and outside university core in relation to genderand sexualities issues, in order to show an interest struggle: thematic, academic, budgetary and political,  within this university unit.
Keywords: gender and sexualities; critic incidents; university field; Bahía Blanca